key MARKETING SKILLS - Peter Cheverton (Kogan Page Limited Second edition, 2004)
It’s not a good start, and unfortunately it gets worse. Arecent opinion poll in the United Kingdom found that marketing folk were rated at only one rung above politicians and tabloid journalists on the ladder of ‘respectable’ careers… but if you want to hear real cynicism, try asking businesspeople what they make of their marketing colleagues. ‘Slippery’ is a common description, ‘unaccountable’ another, with ‘unprofessional’ another regular criticism. Compared to the rigour of an accountant or an engineer or a research scientist, it seems that non-marketers have a hard time seeing any formal process or discipline in the marketer’s activities. It’s not a good start, and unfortunately it gets worse. Arecent opinion poll in the United Kingdom found that marketing folk were rated at only one rung above politicians and tabloid journalists on the ladder of ‘respectable’ careers… but if you want to hear real cynicism, try asking businesspeople what they make of their marketing colleagues. ‘Slippery’ is a common description, ‘unaccountable’ another, with ‘unprofessional’ another regular criticism. Compared to the rigour of an accountant or an engineer or a research scientist, it seems that non-marketers have a hard time seeing any formal process or discipline in the marketer’s activities.